Discurso, mídias digitais e feminismos: a apropriação neoliberal de uma linguagem feminista em enunciados publicitários de produtos de beleza - Fonseca, Amanda Campos (2024)
This research aimed an analysis of how the advertising constructed for a female audience in contemporary times, encountered in social media profiles such as Instagram and TikTok, between the years of 2022 and 2023, especially by beauty brands, appropriates discourses and practices tied in resistance expressions, particularly a feminist one, as a way to update and deepen the power networks, anchored by capitalism and, more specifically, neoliberalism, producing normalization effects of women bodies. Our thought process involved the conditions of possibility of this period’s advertising discourse, analyzing different discursive formations that we encounter in these advertisements: it is our goal to perceive which constructions made in present advertising discourse, through an analysis of the feminist discourse with the aim to target its clients, but that, in reality, may express values and ideas not so different from advertisements made on previous eras in history. For this to happen, this body of work has ties with Foucauldian discourse studies, aiming for an approach that involves the role of memory and history in the formation of discourses. It is important, for this research, foucauldian concepts such as discourse, power, subject, statement, as well as other theoretical constructions that are made possible by Foucault’s archaeology and genealogy works. Our corpus is formed by statements chosen from advertisements made by beauty companies marketed for women, through Instagram and TikTok. The first group of statements analyzed was from the profile Seca Você Renove, on Instagram; the second group was Wrinkles Schminkles, available on TikTok and Instagram; a company that promotes silicone patches that prevent wrinkles and lastly, the third group of statements analyzed was the company O Boticário, on Instagram. Keeping in mind that the advertisements’ target audience is mainly women and utilize a “feminist” voice, our aim is to analyze how statements that subscribe to a feminist discursive formation are appropriated in statements and contexts select by beauty products’ advertisements, reflecting on the power relations’ transformations and present resistance discourse. Furthermore, our work consists in thinking about the materialization of neoliberal values that operate in these statements as a memory effect and that contribute for the construction of a discursive net that articulates important research aspects: capitalism’s influence in society, social media and womanhood in contemporary society.